Training on Making Avocado Leaf Stew (Persea americana Mill.) in Socah Village, Bangkalan Regency - Puji Kurniawati Rahman; Teguh Setiawan Wibowo; Qur’atul Masruroh (Jurnal Pengabdian Masyarakat Bestari, 2023)
The higher prevalence of hypertension in Indonesia is directly proportional to the high cost of treatment. Training on making avocado leaf infusions in Socah Village, Bangkalan Regency, can be an alternative therapy for lowering blood pressure and help the government indirectly handle health and economic issues. This activity uses the lecture method and direct practice, involving ten people from the community who are willing to become participants. The implementation will occur from February 11 to July 16, 2023, beginning with a lecture, followed by direct practice and follow-up activities. Overall, this community service shows good results because of the enthusiasm of the people who are expected to be able to apply it in their daily lives. It was concluded that the people of Socah Village, Bangkalan Regency, could make an infusion of avocado leaves after going through training.